Characterization of pomegranate peel extracts obtained using different solvents and their effects on cell cycle and apoptosis in leukemia cells - Tamborlin, Leticia [UNESP]; Sumere, Beatriz Rocchetti; de Souza, Mariana Corrêa; Pestana, Nathalie Fortes; Aguiar, Ana Carolina; Eberlin, Marcos Nogueira; Simabuco, Fernando Moreira; Rostagno, Maurício Ariel; Luchessi, Augusto Ducati [UNESP] (Wiley, 2020)
Pomegranate (Punica granatum L.) has been used in traditional herbal medicine by several cultures as an anti-inflammatory, antioxidant, antihyperglycemic, and for treatment and prevention of cancer and other diseases. Different parts of the fruit, extraction methods, and solvents can define the chemical profile of the obtained extracts and their biological activities. This study aimed to characterize the chemical profile of peel extracts collected using different extraction solvents and their biological effects on the cell cycle and apoptosis of THP-1 leukemic cells. Aqueous extract presented the highest content of punicalagins (α pun = 562.26 ± 47.14 mg/L and β pun = 1,251.13 ± 22.21 mg/L) and the lowest content of ellagic acid (66.38 ± 0.21 mg/L), and it promoted a significant impairment of the cell cycle S phase. In fact, punicalagin-enriched fraction, but not an ellagic acid-enriched fraction, caused an S phase cell cycle arrest. All extracts increased the number of apoptotic cells. Punicalagin-enriched fraction increased the percentage of cells with fragmented DNA, which was intensified by ellagic acid combination. The treatment combining punicalagin and ellagic acid fractions increased the apoptotic cleaved PARP1 protein and reduced the activation of the growth-related mTOR pathway. Thus, these results evidence that solvent choice is critical for the phenolic compounds profile of pomegranate peel extracts and their biological activities.
Keywords: apoptosis; biological activity; cell cycle; leukemia; pomegranate peel extracts; punicalagin